EKONOMI KREATIF : PEMBERDAYAAN MASYARAKAT MELALUI KERAJINAN KERANG - Ray Octafian; Enik Rahayu (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2022)
Utilization of resources does not only focus on reforms but begins to enter into something that is even more unlimited, namely inspiration, ideas, talents or talents, and creativity. 3 main things form the basis of the creative economy, including creativity, innovation, and invention. To support the creative economy and the condition of the productive age population, the West Kotawaringin Regency government through the tourism office seeks to empower the community through a collaborative activity with one of the universities in Semarang, namely the Indonesian College of Tourism Economics (STIEPARI). The implementation of activities ranging from identification, socialization to independent practice shows that there is an increase in awareness of the training participants to utilize local resources that can be processed into products even though they are made from waste which in this case is shells. This can be seen from the participants' interest in applying the results of the counseling and training and continuing this activity to completion.